Designing Loyalty in Local Banks: The Impact of Brand Image and Service Quality on Satisfaction, Trust, and Repeat Behavior at PT BPR Bank Sleman - Kusworo, Leo Jati; Setiawan, Zunan; Purwoko, Purwoko (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study empirically tests a stimulus–response model that links Brand Image (BI) and Service Quality (SQ) to Customer Loyalty (CL) through the mediating mechanisms of Customer Satisfaction (CS) and Brand Trust (BT) in the context of a regional public bank, PT BPR Bank Sleman (Perseroda). Grounded in expectancy disconfirmation theory and the Stimulus Organism Response framework, the research uses survey data collected from active retail customers and analyzes the hypothesised paths via PLS-SEM. The sample (n 400) was drawn to reflect branch, tenure, and demographic strata typical of BPR clientele. Results indicate that Brand Image and Service Quality both exert significant positive effects on Customer Satisfaction and Brand Trust. Customer Satisfaction and Brand Trust, in turn, strongly predict Repurchase/Revisit Intention and overall Customer Loyalty, confirming their mediating roles. Notably, service quality’s effect on behavioral loyalty is largely indirect operating through satisfaction whereas brand image contributes both directly and indirectly by enhancing trust and setting expectations. Practical implications emphasize that BPRs should coordinate brand positioning with consistent service delivery: investments in frontline training, process reliability, and community-oriented brand narratives yield higher retention than price-only competition. The study contributes theoretically by validating the stimulus organism response chain in a localized banking setting and methodologically by offering a validated measurement battery adapted for BPRs. Limitations include single-institution focus and cross-sectional design. future research should pursue longitudinal and multi-site comparisons to verify temporal stability and generalizability across regional banks.